Relevance status value model of index Islamicus on Islamic history and civilizations - Muhammad Ashraf Ali (Kulliyah of Information and Communication Technology,International Islamic University Malaysia, 2014)
Sorting the retrieved results from the most relevant to the least relevant is the common option of an Information Retrieval System (IRS). This sorting mechanism or relevance judgment is computed by measuring closeness of query with its documents. The purposes of this study were to measure the relevance status of Index Islamicus, evaluate the semantic correlation between a query and documents, and inquire the basis of its rank. Forming up 100 queries on Islamic History and Civilizations, with two indexing elements (keyword and concept), a laboratory experiment was generated on its first 10 items of the rank. Throughout an experimental research design, Relevance Status Value (RSV) formula was used to measure system-computed rank and compare it with Mean Average Precision (MAP). The results showed that the average status value of Index Islamicus ranking on relevance criterion was 18%. Despite several limitations where the study's main focus was only on one subject domain and the items calculated were only 1000, this small percentage of its ranking mechanism proved that semantic correlations between queries with subject domain did not achieve the satisfactory level.